‘When They Struggle, I Cannot Sleep Well Either’: Perceptions and Interactions Surrounding University Student and Teacher Well-Being - Kiltz, Lisa; Rinas, Raven; Daumiller, Martin; Fokkens-Bruinsma, Marjon; Jansen, Ellen P. W. A. (Frontiers in Psychology, 2020)
A wealth of evidence has indicated that both students and teachers experience high levels of stress, burnout, and ultimately compromised well-being in the university context. However, although numerous studies have investigated well-being among university students, and some studies have addressed well-being among university teachers, these lines of research are often conducted in isolation from one another. This is surprising, as the importance of considering reciprocal links between students and teachers has been suggested in numerous empirical studies. Additionally, when researching well-being in academia, conceptualizations of well-being differ from study-to-study. The present research therefore investigated how students and teachers conceptualize well-being at the university based on their personal experiences, as well as how student and teacher well-being interact. To examine this, six university students (50% female), and ten teachers (50% female) from Germany and the Netherlands participated in semi-structured interviews. Qualitative analysis using a multistage coding process revealed detailed insights concerning students’ and teachers’ perceptions of well-being that coincided with positive psychology, resilience, multifaceted, and basic psychological need fulfillment approaches. Moreover, an interaction between students’ and teachers’ well-being became apparent, including several factors such as the student-teacher relationship, that contributed to both population’s well-being. The present findings lend evidence towards a more coherent conceptualization of well-being for further research and are discussed in terms of suggestions for initiatives that simultaneously support both populations, for example, through the student-teacher relationship.